2021
DOI: 10.3389/fmicb.2021.615416
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Intestinal Microbial Community and Hematological Profile in Native Tibetans and Han Immigrants

Abstract: Hematological features are one of the best-known aspects of high-altitude adaptation in Tibetans. However, it is still unclear whether the intestinal microbiota is associated with the hematology profile. In this study, routine blood tests and 16S rRNA gene sequencing were used to investigate the differences in the intestinal microbiota and hematological parameters of native Tibetan herders and Han immigrants sampled at 3,900 m. The blood test results suggested that the platelet counts (PLTs) were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 88 publications
2
10
0
Order By: Relevance
“…These findings are consistent with our findings. The results of Ma (59) showed that the relative abundance of Megamonas in people in the plains area was higher than that in people in the high-altitude area, consistent with the conclusion of our study. The reason may be related to the impairment of gastrointestinal mucosal barrier function caused by hypoxia, but research on the mechanism is still incomplete.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with our findings. The results of Ma (59) showed that the relative abundance of Megamonas in people in the plains area was higher than that in people in the high-altitude area, consistent with the conclusion of our study. The reason may be related to the impairment of gastrointestinal mucosal barrier function caused by hypoxia, but research on the mechanism is still incomplete.…”
Section: Discussionsupporting
confidence: 91%
“…In their review of the effects of lifestyle and environment on the human microbiome, Gupta et al (2017) asserted that urbanization—which generally includes adoption of a more indoor‐based lifestyle, improved sanitation and living conditions and less exposure to nature—plays a predominant role in microbial shifts among immigrants who migrate to Westernized countries. Tibetan natives had higher gut microbial diversity than Chinese Han immigrants who had lived in Guoluo (high‐altitude area) for about a year, showing that when immigrants move from industrialized areas to non‐industrialized areas, they retain several features of their pre‐migration microbiome (Ma et al, 2021). The gut microbiomes of the Tibetan natives were more enriched with bacteria related to carbohydrate metabolism when compared to the Han immigrants.…”
Section: Resultsmentioning
confidence: 99%
“…Published by Francis Academic Press, UK -43-Tibetans, but the differences were not statistically significant (p > 0.05) (2). A meta-analysis included 13 studies on the relationship between intestinal flora and IBS, involving 360 patients with IBS and 268 healthy subjects.…”
Section: At the Genus Levelmentioning
confidence: 99%